I'm glad I did - Weil, Cynthia (Soho Teen, 2015)
In 1963 sixteen-year-old JJ Green, a songwriter interning at New York City's famous Brill Building, finds herself a writing partner in Luke Silver, a boy who seems to connect instantly with her music, and they start cutting their first demo with Dulcie Brown, a legend who's fallen on hard times, with a secret past.